The Effect of Serving Speed and Menu Diversity on Con-sumer Buying Interest at The Anugrah Padang Bulan Rantau Prapat Board, Labuhanbatu Regency - Nurul Aini Ritonga; Sri Ayla; Iskandar Muda Sipayung (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study was to determine the significant effect or not of the speed of presentation and menu diversity on consumer purchasing interest at Pondok Anugrah Padang Bulan Rantauprapat, Labuhan Batu Regency. The study used quantitative methods and through an associative causality ap-proach. The data collection technique used was through observation and interviews. The sample in this study was 88 respondents or consumers. The sampling technique was simple random sampling. The data analysis technique used statistical techniques / SPSS by conducting validity and reliability tests then for questionnaires and multiple linear regression analysis with the T Test and F Test to prove the hy-pothesis. The results showed that there was a close and significant effect of the speed of presentation on consumer purchasing interest, there was a close and significant effect of menu diversity on consumer purchasing interest, the effect of the speed of presentation and menu diversity was 97.6% and the re-maining 2.3% was influenced by other factors and variables.